(-3/2)6 * (4/9)3 = (1/2)3x

(-3/2)6 * (4/9)3 = (1/2)3x
 

(-3/2)6 * {(2)2/(3)2}3 = (1/2)3x

(-3/2)6 * (2/3)3*2 = (1/2)3x

(-3/2)6 * (2/3)6 = (1/2)3x

{(-3/2)*(2/3)}6 = (1/2)3x

(-1)6 = (1/2)3x

1 = 1/23x

23x = 1

8x = 1

=> x = 0

(because anything power 0 is 1)

  • 2
thanks for solution😊😊😊😊
  • 0
(-3/2)6 * (4/9)3 = (1/2)3x
 

(-3/2)6 * {(2)2/(3)2}3 = (1/2)3x

(-3/2)6 * (2/3)3*2 = (1/2)3x

(-3/2)6 * (2/3)6 = (1/2)3x

{(-3/2)*(2/3)}6 = (1/2)3x

(-1)6 = (1/2)3x

1 = 1/23x

23x = 1

8x = 1

=> x = 0

(because anything power 0 is 1)

  • 0
(-3/2)6 * (4/9)3 = (1/2)3x (-3/2)6 * {(2)2/(3)2}3 = (1/2)3x (-3/2)6 * (2/3)3*2 = (1/2)3x (-3/2)6 * (2/3)6 = (1/2)3x {(-3/2)*(2/3)}6 = (1/2)3x (-1)6 = (1/2)3x 1 = 1/23x 23x = 1 8x = 1 => x = 0
  • 1
What are you looking for?